2021
DOI: 10.3390/jmmp6010004
|View full text |Cite
|
Sign up to set email alerts
|

Review on Additive Manufacturing of Multi-Material Parts: Progress and Challenges

Abstract: Additive manufacturing has already been established as a highly versatile manufacturing technique with demonstrated potential to completely transform conventional manufacturing in the future. The objective of this paper is to review the latest progress and challenges associated with the fabrication of multi-material parts using additive manufacturing technologies. Various manufacturing processes and materials used to produce functional components were investigated and summarized. The latest applications of mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 156 publications
(203 reference statements)
1
67
0
Order By: Relevance
“…Additive manufacturing (AM) is a genuine process of joining materials layer by layer from a digitalised model [ 1 ]. The growing interest on additive manufacturing is justified by numerous advantages, among are which the high level of complexity, the weak dependence to tooling, the local control of the structure, and the customisation of the realisations [ 2 ]. According to the review paper by Hasanov et al [ 2 ], AM can be a key technology for transformation of conventional manufacturing, allowing for the production of functionally graded materials, for instance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive manufacturing (AM) is a genuine process of joining materials layer by layer from a digitalised model [ 1 ]. The growing interest on additive manufacturing is justified by numerous advantages, among are which the high level of complexity, the weak dependence to tooling, the local control of the structure, and the customisation of the realisations [ 2 ]. According to the review paper by Hasanov et al [ 2 ], AM can be a key technology for transformation of conventional manufacturing, allowing for the production of functionally graded materials, for instance.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest on additive manufacturing is justified by numerous advantages, among are which the high level of complexity, the weak dependence to tooling, the local control of the structure, and the customisation of the realisations [ 2 ]. According to the review paper by Hasanov et al [ 2 ], AM can be a key technology for transformation of conventional manufacturing, allowing for the production of functionally graded materials, for instance. Several processing routes fall within the definition of AM technology, such as Fused Filament Fabrication (FFF)/Fused Deposition Modelling (FDM) [ 3 ], or selective laser sintering (SLS) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The capability of application of two or more materials in one single process plays an important role for AM method for cost effective and production rate efficient fabrication of multimaterial FGMs. Hasanov et al [73] published a comprehensive review that deals with the state-of-art and main challenges of multi-material fabrication with all AM methods. They pointed out that improvements should be done in development of suitable software, characterization of optimal transition zones, large-scale manufacturing capability, materials that allow different combinations and printer design.…”
Section: Additive Manufacturing Of Functionally Graded Materialsmentioning
confidence: 99%
“…Lack of guidelines and standards for the selection of best AM method in terms of characterization of grading in materials Commercial methodologies for the mass production via AM methods Hasanov et al [73] reported in their review article that improvements in following points are needed for the design and manufacturing of complex FGMs.…”
mentioning
confidence: 99%
“…AM was described and patented for the first time by Chuck Hull in the early 1980s [4]. AM technology has demonstrated a great ability to manufacture pieces from ceramic [5][6][7], metallic [8][9][10], and polymeric powders [11][12][13], as well as their mixtures [14,15], for diverse applications by directly extracting the geometric data from computer-aided design (CAD) models [16,17]. In comparison to traditional manufacturing methods, AM can produce complex-shaped objects with a simple production process, high flexibility, shorter production time, minimal waste of material, low cost, and near-net-shape results [18][19][20].…”
Section: Introductionmentioning
confidence: 99%